Allylic and Allenylic Dearomatization of Indoles Promoted by Graphene Oxide by Covalent Grafting Activation Mode. Issue 46 (20th July 2020) - Lombardi, Lorenzo; Bellini, Daniele; Bottoni, Andrea; Calvaresi, Matteo; Monari, Magda; Kovtun, Alessandro; Palermo, Vincenzo; Melucci, Manuela; Bandini, Marco
Abstract: The site‐selective allylative and allenylative dearomatization of indoles with alcohols was performed under carbocatalytic regime in the presence of graphene oxide (GO, 10 wt % loading) as the promoter. Metal‐free conditions, absence of stoichiometric additive, environmentally friendly conditions (H2 O/CH3 CN, 55 °C, 6 h), broad substrate scope (33 examples, yield up to 92 %) and excellent site‐ and stereoselectivity characterize the present methodology. Moreover, a covalent activation model exerted by GO functionalities was corroborated by spectroscopic, experimental and computational evidences. Recovering and regeneration of the GO catalyst through simple acidic treatment was also documented. Abstract : Graft on ! The covalent "catalysis" exerted by graphene oxide on the site‐selective dearomatization of indoles with allylic/propargylic alcohols is presented under metal‐, additive‐ and anhydrous‐free conditions (see scheme).